MESIN PENGOLAH MINUMAN KESEHATAN INSTAN UNTUK HOME INDUSTRY HEALTHY DESA LIMBANGAN KECAMATAN LIMBANGAN KABUPATEN KENDAL - Kriswanto, Kriswanto; Widodo, Rahmat Doni (Universitas Negeri Semarang, 2017)
Quality and production capacity of instant health beverages HEALTHY home industry needs to be im- proved by using instant beverage processing machines. Destination activities to the community ser- vice are: 1) to improve the quality and production capacity of the processing machine instant health drink. ; 2) determine the added value from the use of instant health beverage processing machines;3) designing product packaging instant health drink exciting HEALTHY home industry. Benefits of community service activities are: increasing the value-added plant rhizomes; generating appropri- ate technologies such as instant health machine processing machine; improve the performance of HEALTHY home industry to become more optimal; assist local governments in an effort to improve the quality of life through community service activities. The method of implementation of activities, among others: 1) extension of instant health beverage processing; 2) manufacture of packaging design by using graphic design; 3) making machines using the method of design; 4) training in production, use of tools and treatment methods and practices FAQ; 5) evaluation of the use of the machine using a test method and observation; 6) assistance and consultation methods of discussion. The results of these activities are there to improve the quality and production capacity by using a processing engine instant drinks, deficits improve the added value of the application of machinery to come from reduced labor costs of employees, and a reduction in fuel costs reached lebh of 50% where the process previ- ously done twice into one time. Health beverage product packaging design has been made with credit instant composition, manner of presentation, production, brand, net weight, and the P-IRT permits